Efecto de la sustitución del nitrito de sodio con aceite de romero en la calidad final de una jamonada - Prado Lucas, Jorge Alayn (2017)
The objective of this research was to evaluate the effect of the essential oil of rosemary in a partial substitution with the sodium nitrite in the elaboration of a jamonada in order to determine the final quality of the sausage through the microbiological evaluation, physicochemical and sensorial characteristics. The study factors were two concentrations of rosemary oil (200 ppm, 400 ppm) and two concentrations of Sodium Nitrite (50 ppm, 100 ppm). In the microbiological analysis the total count of mesophilic aerobic bacteria was established where there was a significant increase in the control that presented the highest amount with 2.4x102 that according to the Dunnett test showed statistically significant differences (p <0.05) between the treatments and the control sample, and showing absence in the bacteria escherichia coli, salmonella, staphylococcus aureus, molds, yeasts and clostridium botulinum. The physicochemical analysis included the instrumental texture profile (TPA) in which the adhesiveness, cohesiveness, gum, elasticity, hardness and mastication were analyzed. According to the Dunnett test, statistically significant differences were found (p <0.05) for the variables gum and chewiness in the treatments and control samples. The samples of the T4 treatment showed the highest value in terms of buds with a value of 11.45 (Kg m s2), which means that it is harder to taste since it does not disintegrate easily and in the sensorial attributes the rosemary oil gave a very pleasant smell and taste in all its treatments.